Bed topography of Princess Elizabeth Land in East Antarctica - Cui, X; Jeofry, H; Greenbaum, JS; Guo, J; Li, L; Lindzey, LE; Habbal, FA; Wei, W; Young, DA; Ross, N; Morlighem, M; Lenneke Jong; et al. (2020)
We present a topographic digital elevation model (DEM) for Princess Elizabeth Land (PEL), East Antarctica. The DEM covers an area of ∼900 000 km 2 and was built from radio-echo sounding data collected during four campaigns since 2015. Previously, to generate the Bedmap2 topographic product, PEL's bed was characterized from low-resolution satellite gravity data across an otherwise large (>200 km wide) data-free zone. We use the mass conservation (MC) method to produce an ice thickness grid across faster flowing (>30 m yr −1 ) regions of the ice sheet and streamline diffusion in slower flowing areas. The resulting ice thickness model is integrated with an ice surface model to build the bed DEM. Together with BedMachine Antarctica and Bedmap2, this new bed DEM completes the first-order measurement of subglacial continental Antarctica – an international mission that began around 70 years ago. The ice thickness data and bed DEMs of PEL (resolved horizontally at 500 m relative to ice surface elevations obtained from the Reference Elevation Model of Antarctica – REMA) are accessible from https://doi.org/10.5281/zenodo.4023343 (Cui et al., 2020a) and https://doi.org/10.5281/zenodo.4023393 (Cui et al., 2020b).